2016
DOI: 10.1111/andr.12179
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile ofPLCζ,PAWP,andTR-KITin association with fertilization potential, embryo development, and pregnancy outcomes in globozoospermic candidates for intra-cytoplasmic sperm injection and artificial oocyte activation

Abstract: SUMMARYSperm-mediated oocyte activation critically depends upon appropriate expression and assembly of sperm-borne oocyte-activating factors (SOAFs) during spermiogenesis. Several factors have been considered as candidate for SOAFs over the recent years. However, little is known about the expression profile of these candidates and their potential contribution to the clinical outcomes of intra-cytoplasmic sperm injection (ICSI), particularly in globozoospermia. This study investigated the expression profile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 48 publications
2
31
1
1
Order By: Relevance
“…In the light of these considerations, we also showed that expression level of PLCζ mRNA were significantly lower in infertile men with previous failed fertilization and globozoospermia than fertile individuals [12]. Other researchers also observed the absence or low expression of PLCζ protein in infertile men with globozoospermia and concluded that this factor could be considered as a prognostic marker of oocyte activation [12,18,20]. Recent studies have demonstrated that sperm factors involved in oocyte activation are sensitive to heat treatment or cold shock during freeze-thawing [21,22].…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…In the light of these considerations, we also showed that expression level of PLCζ mRNA were significantly lower in infertile men with previous failed fertilization and globozoospermia than fertile individuals [12]. Other researchers also observed the absence or low expression of PLCζ protein in infertile men with globozoospermia and concluded that this factor could be considered as a prognostic marker of oocyte activation [12,18,20]. Recent studies have demonstrated that sperm factors involved in oocyte activation are sensitive to heat treatment or cold shock during freeze-thawing [21,22].…”
Section: Introductionsupporting
confidence: 50%
“…Densitometric analysis of the images was performed by Quantity One Software v 4.6.9 (Bio-Rad, Munchen, Germany). Results were expressed as mean relative intensity [20].…”
Section: Assessment Of Plcζ Expression By Western Blotmentioning
confidence: 99%
“…Successful ART outcomes by resorting to some new treatment protocols/techniques along with ICSI, such as ICSI with AOA using calcium ionophore, may help overcome male infertility in patients with total globozoospermia (Abadi, Tavalaee, Shahverdi, & Nasr‐Esfahani, ; Karaca et al, ; Kochhar & Ghosh, ; Shang et al, ; Tavalaee et al, ). Some candidate genes such as truncated Kit, PLC ζ and post‐acrosomal sheath WW domain‐binding protein (PAWP) are found to be responsible for oocyte activation during fertilisation (Abadi et al, ; Haghighat et al, ; Tavalaee & Nasr‐Esfahani, ). Significantly lower expression profiles of these genes and their corresponding proteins in globozoospermic men have been reported, suggesting a beneficial effect of AOA resulting in higher fertilisation rates after conventional ICSI (Abadi et al, ; Haghighat et al, ; Tavalaee & Nasr‐Esfahani, ; Taylor et al, ).…”
Section: Fertilisation Potential and Treatmentsmentioning
confidence: 99%
“…Fertilisation failure by round‐headed sperm after ICSI can be mainly attributed to deficiency or absence of sperm factors, which are essential for oocyte activation. In this regard, several studies indicate that expression of sperm‐specific phospholipase C (PLCζ) as a major sperm oocyte‐activating factor were very low or absent in round‐headed sperm in comparison with normal sperm (Amdani, Jones, & Coward, ; Chansel‐Debordeaux, Dandieu, Bechoua, & Jimenez, ; Kamali‐Dolat Abadi, Tavalaee, Shahverdi, & Nasr‐Esfahani, ; Tavalaee & Nasr‐Esfahani, ; Taylor et al.,). Moreover, thirteen genes are known to be involved in acrosome biogenesis process and possibly their deficiency can be detected in round‐headed sperm.…”
Section: Introductionmentioning
confidence: 99%